Study on behaviors of PO43- in the sediment of the West Lake using isotope trace technique - TANG Meng-cheng (浙江大学学报. 农业与生命科学版)
Under laboratory condition, the technique of the isotope trace was applied to investigate 32P-PO43- behaviors in water/sediments of the West Lake. The results showed that 32P-PO43- in water/sediments declined exponentialy with time. 32P-PO43- in the sediments can release into overlying water. Exchangable (E) phosphorus in the sediments was about 78 μg/g to 184 μg/g sediments. Form of phosphate in the sediments could be changed. Most of PO43- could be changed into unsolvable phosphate in 15 days